Report : "A Study Of The Misuse Of Drugs Among Secondary School Children In The State Of Penang And Selangor. - Spencer, Dr. C. P.; Navaratnam, Profesor Madya (Dr.) V. (Pusat Penyelidikan Dadah Dan Ubat-Ubatan Universiti Sains Malaysia, 1976)
Drugs in a non-medical setting, used to alter mood, perception or consciousness are the topic of the present report: the report and the study upon which it is based reflect a widespread feeling in society that the use of such drugs is in itself a cause for concern, that the presumed increase in such use by young people heightens this concern~ but that response to drug usage which is ill informed is unlikely to achieve desirable ends.